Oil palm boom: its socioeconomic use and abuse - Sibhatu, Kibrom T. (Frontiers in Sustainable Food Systems, 2023)
Oil palm cultivation has experienced explosive expansion in recent decades. Although expansion has serious environmental and socioeconomic consequences, only environmental issues have garnered attention in public discussion and synthesis studies. In this study, we synthesized the literature on the socioeconomic impacts of oil palm expansion across various observation units and spatial and temporal scales, which is of significant relevance to policymakers, researchers, and the wider public. Our review demonstrates that oil palm expansion is a double-edged sword from a socioeconomic perspective. On the one hand, it has substantially benefited producing and non-producing countries’ export economies by (re)exporting crude palm oil and its derivatives and creating employment opportunities. This has stimulated rural economies, led to rural poverty reduction, and improved food security and diets for rural households in producer countries. On the other hand, the crop’s expansion has increased conflicts and tension between local communities and agro-industrial companies, worsened workers’ conditions, and widened domestic economic inequality between producing and non-producing areas within a given producer country. The direct income benefits through harvest sales and employment are more evident in the Southeast Asia production frontier, where oil palm cultivation and marketing are relatively advanced and well-integrated into international value chains. The negative outcomes are observed in all oil palm production regions, with more negative effects on food security in the African production frontiers. We propose multiple actionable research and policy recommendations that may jointly lead to inclusive and sustainable socioeconomic (and environmental) outcomes in oil palm cultivation. The socioeconomic consequences of oil palm expansion at the global level, in the African and American production frontiers, and the role of gender in palm oil production systems remain understudied. Hence, studies should be conducted.